Poverty and yield effects of CGIAR maize varieties in smallholder farming systems of Zambia - Ngoma, Hambulo; Setimela, Peter; Silva, João Vasco; Krishna, Vijesh (Wiley Periodicals LLC., 2025)
Improved germplasm is a recognized adaptation strategy to climate change. We assessed the adoption, and impacts of CGIAR maize varieties on livelihoods in Zambia using fixed effects regression and a difference-in-differences framework. Three-waves of nationally representative panel data indicate that 24% of smallholders used CGIAR germplasm on about 225,000 hectares in 2019. Relative to other non-CGIAR maize varieties, the use of CGIAR maize varieties was associated with 26–35% yield increase, and 2–10% reduction in the depth of poverty on average. Thus, while improved varieties can increase crop productivity effectively, they are not substitutes for broad-based poverty reduction strategies.